Essential oils of the leaves and stems of four Psidium spp - Silva, João Domingos da; Luz, Arnaldo Iran R.; Silva, Milton Hélio L da; Andrade, Eloísa Helena de Aguiar; Zoghbi, Maria das Graças Bichara; Maia, José Guilherme Soares (Flavour and Fragrance Journal, 2003)
The essential oils of the leaves and fine stems of Psidium acutangulum, P. striatulum, P. guineense and P. guajava were obtained by hydrodistillation and analysed by GC-MS. The main compounds identified in the oil of P. acutangulum were α-pinene (14.8%), 1,8-cineole (12.9%) and β-pinene (10.1%). The oil of P. striatulum was dominated by β-caryophyllene (28.6%), α-selinene (7.7%), caryophyllene oxide (7.6%) and β-selinene (7.4%). The major constituents found in the oil of P. guineense were β-bisabolol (17.4%), limonene (6.8%) and epi-α-bisabolol (6.7%). The oil of P. guajava was dominated by α-pinene (23.9%), 1,8-cineole (21.4%) and β-bisabolol (9.2%). Copyright © 2003 John Wiley & Sons, Ltd.
Keywords: Composition; Distillation; Gas Chromatography; Mass Spectrometry; Plants (botany); Hydrodistillation; Essential Oils; 2 Hexenal; Benzaldehyde; Bisabolol; Borneol; Bornyl Acetate; Camphene; Carveol; Caryophyllene; Caryophyllene Oxide; Cineole; Cuminaldehyde; Essential Oil; Geraniol; Humulene; Limonene; Linalool; Myrcene; Para Cymene; Phenethyl Alcohol; Pinene; Plant Extract; Propionaldehyde; Psidium Extract; Safrole; Terpinen 4 Ol; Terpinene; Terpineol; Terpinolene; Thymol; Unclassified Drug; Unindexed Drug; Analytic Method; Chemical Analysis; Chemical Composition; Chemical Procedures; Controlled Study; Distillation; Gas Chromatography; Guava; Mass Spectrometry; Medicinal Plant; Nonhuman; Plant Leaf; Species Diversity; Myrtaceae; Psidium; Psidium Guajava; Psidium Guineense